Coding for penetration testers building better tools - Andress, Jason; Linn, Ryan (Syngress, 2017)
Coding for Penetration Testers: Building Better Tools, Second Edition provides readers with an understanding of the scripting languages that are commonly used when developing tools for penetration testing, also guiding users through specific examples of custom tool development and the situations where such tools might be used. While developing a better understanding of each language, the book presents real-world scenarios and tool development that can be incorporated into a tester's toolkit. This completely updated edition focuses on an expanded discussion on the use of Powershell, and includes practical updates to all tools and coverage